Analisis Tingkat Keterserapan Lulusan Kelas Industri Samsung dari Jurusan Rekayasa Perangkat Lunak SMK Turen ke Perusahaan Samsung - Erma Widayanti; Wahyu Sakti Gunawan Irianto; Heru Wahyu Herwanto (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The purpose of this study is to determine the implementation of the Samsung Tech Institute Industrial Class learning process at SMK Turen and to find out the factors that cause the low absorption of Samsung Tech Institute Industrial Class graduates to Samsung companies and get recommendations in order to increase the absorption of Samsung Tech Institute Industrial Class graduates in Samsung Companies. This type of research uses descriptive qualitative research methods with data collection using documentation, observation and interview techniques and is supported using questionnaire data which is validated by triangulation data. The results of the study, the school has made various efforts to equip students to be ready to enroll in the Samsung Company both from the curriculum and learning modules and programs that support the improvement of students' competencies in the world of work and in conclusion samsung industrial class graduates experience reluctance to register or apply for jobs at the Samsung Company, due to low motivation and many graduates feel anxious about facing the strict rules and work demands make them hesitate and lack of understanding that employment opportunities at Samsung can offer many career benefits in the future.